A MATHEMATICAL MODEL OF A LEGO DIFFERENTIAL DRIVE ROBOT - Gheorghe GÎLCĂ; BÎZDOACĂ Nicu George, (Fiabilitate şi Durabilitate)
This paper details the development of a model for a mobile robot constructed from Lego® Mindstorms®. The equations representing the dynamics and kinematics of the robot are derived. In addition, the motors and wheels are represented in the model. The mobile robot is programmed in graphical programming language NXT-G and can follow a black line without problems, even if the route to achieve is difficult.